RESPON RUSIA TERHADAP PEMBANGUNAN BALLISTIC MISSILE DEFENSE (BMD) AMERIKA SERIKAT DI EROPA - Anugrah, Kharisma Ridho; Pinatih, Ni Komang Desy Arya (Jurnal Transformasi Global, 2019)
AbstractThe dynamics of bilateral relations between United States and Russia is characterized by confrontation and rivalry patterns, thus an aggressive action done by one party will stimulate  strategic response of other party. In the early 2000’s, United States stimulated tension with Russia through its policy to build Its Ballistic Missile Defese (BMD) in European Countries such as Poland, Czech, Romania, Turkey, and Mediteranian Sea. This policy was interpreted as a threat by Russia, and as Its strategic response, Russia strengthened Its alliance with Collective Security Treaty Organization (CSTO) through formation of military cooperation named Collective Rapid Reaction Force (CRRF).This research will discuss about how is Russian response to offset threat presented by United States through Its BMD in Europe. This research uses Balance of Threat Theory (BoT) by Stephen M. Walt as main analysis tools. Through the implementation of BoT’s variables such as aggregate power, geographical proximity, offensive power, and aggressive intention, this research is able to explain the United States’ source of threat to Russia and determine Its response to offset this threat in form of alliance, whether balancing or bandwagoning. Keywords: Threat, Alliance, Balancing, Bandwagoning, United States, Russia